Local lives and global transformations : towards world society - Kennedy, Paul T., 1941- (Houndmills, Basingstoke, Hampshire : Palgrave MacMillan, 2010)
'How does globalization impact upon our personal lives? What are its boundaries? This book examines how local and global studies interact. Filled with case studies and empirical research that show the ways in which real local lives function under global conditions, this book helps students push the boundaries of their understanding of globalization'--Provided by publisher.
Introduction : global and local -- Global transformations -- Theorizing globalization : linking the world -- The global economy : fragmented workers, mobile capital -- Migrants ; key agents of globalization -- Transnational criminals and terrorists : new insecurities -- Local lives -- The resilient local : critiquing the idea of the hegemonic global -- The continuing appeal of local, bubble lives : case studies -- Asserting and protecting local lives : urban and rural resistance -- Paths towards a world society -- Globality and world society : micro-actions and interpersonal relations.
Includes bibliographical references and index.
Keywords: Globalization -- Social aspects; Multiculturalism; Intercultural communication